VP16 Interventional Management Of Hyperhidrosis: A Systematic Review. (12th January 2018) - Llewellyn, Alexis; Jones-Diette, Julie; Wright, Kath; Rice, Stephen; Moloney, Eoin; Stoniute, Julija; Layton, Alison; Levell, Nick; Stansby, Gerard; Craig, Dawn; Woolacott, Nerys; Wade, Ros
Abstract : INTRODUCTION: Hyperhidrosis is characterized by uncontrollable excessive sweating, which occurs at rest, regardless of temperature, and can significantly affect quality of life. There is substantial variation in the availability of treatments in secondary care and uncertainty regarding optimal patient management. A systematic review was undertaken to assess the clinical effectiveness of treatments prescribed by dermatologists (iontophoresis, anticholinergic medications, botulinum toxin injections) and minor surgical treatments (curettage and newer energy based technologies) for primary hyperhidrosis and identify areas for further research. METHODS: Fifteen databases and trial registers were searched to July 2016. Pairwise meta-analyses were conducted for comparisons between botulinum toxin injections and placebo for axillary hyperhidrosis. For other treatments data were synthesised narratively due to limited and heterogeneous data. RESULTS: Fifty studies were included in the review; thirty-two randomized controlled trials (RCTs), seventeen non-RCTs and one case series. There was substantial variation between the studies in terms of country of origin (indicating climate and population differences), interventions and methods of outcome assessment. Most studies were small, at high risk of bias and poorly reported. There was moderate quality evidence of a large statistically significant effect of botulinum toxin injections on axillary hyperhidrosis symptoms in the short to medium term (up to 16 weeks), compared with placebo. There was weak but consistent evidence for iontophoresis for palmar hyperhidrosis. Evidence for other interventions was low or very low quality. Combining the evidence and patient advisor input, we established that further research on the clinical and cost-effectiveness of botulinum toxin injections (with anesthesia) versus iontophoresis for palmar hyperhidrosis would be useful. CONCLUSIONS: The evidence for the effectiveness and safety of treatments for primary hyperhidrosis is limited overall and few firm conclusions can be drawn. However, there is moderate quality evidence to support the use of botulinum toxin injections for axillary hyperhidrosis. A trial comparing botulinum toxin injections with iontophoresis for palmar hyperhidrosis is warranted.